A complicated decentralisation: The institutional landscape of Poland’s system of public services - Sześciło, Dawid (Journal of Public Governance, 2016)
Decentralisation has been one the pillars of the institutional reforms taking place in Poland over the last 25 years. It gave local and regional governments an important role in managing the provision of key public services, including healthcare and education. However, the actual scope of the decentralisation achieved in both areas of public services has been rather limited, and this is especially true of healthcare. Furthermore, the complexity of the current institutional landscape in the governance of education and healthcare hampers the setting of any clear lines of accountability. The article thus discusses key challenges associated with a limited and confusing model of decentralisation, including the triggering of blame games between central and local government, the enhanced privatisation of public services and the lack of a consensual and deliberative policymaking culture in public-services delivery.